All's fair in love and scandal ebook - Linden, Caroline (Scandalous, 2015)
Nothing wagered... Douglas Bennet can't resist a good wager, especially not one that involves a beautiful woman. When a friend proposes an audacious plan to expose the most notorious woman in England, Douglas agrees at once. After all, it would be quite a coup to discover the true identity of Lady Constance, author of the infamous erotic serial scandalizing the ton, 50 Ways to Sin. Nothing won... Madeline Wilde is used to being pursued. For years she's cultivated a reputation for being unattainable and mysterious, and for good reason: her livelihood depends on discretion. When Douglas turns his legendary charm on her, she dismisses him as just another rake. But he surprises her—instead of merely trying to seduce her, he becomes her friend...her confidant...and her lover. But can it really lead to happily-ever-after...or are they about to become the biggest scandal London has ever seen?